The Effect of Profitability, Leverage, and Liquidity on Tax Avoidance: Pengaruh Profitabilitas, Leverage, dan Likuiditas terhadap Tax Avoidance - Firnanda Almas Julia Aditama; Untung Wahyudi; Khojanah Hasan; Muhammad Syafiq (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
The essence of this case study is to evaluate the impact of a company's financial components on tax avoidance practices. These financial components are represented by profitability, leverage, and liquidity. Observational data were taken from issuers listed on the Indonesia Stock Exchange (BEI) during the period 2021 to 2023. The total number of observations covers 21 companies obtained using a purposive sampling technique. The data is secondary and was obtained from annual financial reports available on the official BEI website and the official websites of the related companies. Data processing was carried out using Eviews software version 13, which includes descriptive statistics, regression model selection tests (Chow test, Hausman test, and Lagrange Multiplier test), and hypothesis testing. The study findings indicate that partially, profitability has a significant negative effect and leverage has a significant positive effect on tax avoidance, while liquidity has no effect. Simultaneously, all three variables are found to have a positive effect on tax avoidance. The results of this case study can provide a number of practical recommendations. Thus, this case study not only makes an empirical contribution to the finance and taxation literature but also has applied implications for decision-making at the managerial, regulatory, and investor levels.